TO THE ISSUE OF IMPROVING OF LEGAL REGULATION OF RELATIONS IN THE AREA OF ATTRACTION OF PUBLIC SERVICE EMPLOYEES TO DISCIPLINARY RESPONSIBILITY - Логвиненко, Аліса Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
The article analyses theoretical problems and problems of legal regulation of relations in the field of attracting public service employees to disciplinary responsibility. The generalizing character of the category «public service» is indicated and the necessity of theoretical definition and consolidation of the notion of service discipline in normative legal acts regulating the passage of certain types of public service is substantiated. The types of public service are highlighted. Such types are: civil service, service in local self-government bodies, militarized public service, service in prosecutor’s offices. There emphasized that relations regarding the employment of a judge, the dismissal of a judge from office and the termination of his powers, disciplinary liability of a judge, and the application of legal restrictions on a professional judge are covered by the public service. The important factors that influence the existence of the peculiarities of the application of disciplinary responsibility are identified: the nature of tasks and functions performed by certain categories of public service employees, the nature of the duties for the post and the nature of the civil service. It is grounded that the unification of procedures for bringing to disciplinary responsibility of public service employees should be carried out only within the limits of certain types of public service. The concomitant problem that need to be resolved - is the differentiation between disciplinary and administrative liability for certain categories of public service employees is highlighted.